2011
DOI: 10.1021/jp110538g
|View full text |Cite
|
Sign up to set email alerts
|

Twinned Structure and Growth of V-Shaped Silver Nanowires Generated by a Polyol−Thermal Approach

Abstract: This study demonstrates the details on the twinned structure and growth process of V-shaped silver nanowires with different bending angles (e.g., 90°, 120°, and 135°) confirmed by high-resolution transmission electron microscopy (HRTEM). These nanowires could be synthesized by a facile but effective polyol−thermal reaction method in autoclaves (160−180 °C). The nearly uniform-size silver nanowires show an average diameter of ∼45 nm and length up to tens of micrometers. The microstructure and optical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 88 publications
2
18
1
Order By: Relevance
“…Figure shows the HRTEM images of a single nanocable with an Ag core of ≈20 nm in diameter and a sheath thickness of 18 nm (Figure a). By carefully inspecting the tip of the nanocable (Figure b), it was found that the Ag core is dominated by {110} and {111} crystallographic planes with a growth direction of ⟨001⟩, in good agreement with the previous reports on the Ag nanowires synthesized by hydrothermal method . However, the carbonaceous sheath of the nanocables, acting as surface coating and shape controller of silver wires, has no crystalline but amorphous features, which is different from those of carbon nanotubes or graphene obtained under high‐temperature treatments …”
Section: Resultssupporting
confidence: 86%
“…Figure shows the HRTEM images of a single nanocable with an Ag core of ≈20 nm in diameter and a sheath thickness of 18 nm (Figure a). By carefully inspecting the tip of the nanocable (Figure b), it was found that the Ag core is dominated by {110} and {111} crystallographic planes with a growth direction of ⟨001⟩, in good agreement with the previous reports on the Ag nanowires synthesized by hydrothermal method . However, the carbonaceous sheath of the nanocables, acting as surface coating and shape controller of silver wires, has no crystalline but amorphous features, which is different from those of carbon nanotubes or graphene obtained under high‐temperature treatments …”
Section: Resultssupporting
confidence: 86%
“…This further supports the idea that these are joined, and not deformed wires because the outer surface of a deformed wire would be one continuous curve (not two curved surfaces as shown in Figure d). These structures differ from the previously reported V‐shaped Ag NWs which formed due to twinned crystal plane induced growth and crystal lattice match induced fusion during polyol‐thermal synthesis process . It should be noted that these nanojunctions were formed at room temperature after the washing process without any heat input.…”
contrasting
confidence: 82%
“…Due to instrument limitations, it was not possible to assign the diffraction spots to a particular pattern associated with the face centered cubic (fcc) crystalline silver. 33 In addition to this, the coexistence of a few larger nanoparticles may contribute to the secondary diffraction spots, owing to the presence of twinned crystals (ESI, Fig. S6 †).…”
Section: Characterization Of Silver Nanoparticlesmentioning
confidence: 99%